Methodology for determining the correlation of the clinical efficacy of therapy with the addition of a drug (for example, anti-asthma therapy in children) - Olga V. Zhukova (Belgorod National Research University, 2019)
Introduction: In the recent years, much attention has been paid to the use of leukotriene receptor antagonists (LTRA) in the treatment of bronchial asthma (BA). It has been even proposed to use them as alternatives to hormone therapy. Yet, there are studies demonstrating the advantage of montelukast as similar to placebo. The objective was to create a methodology for determining the correlation of the clinical efficacy of therapy with the addition of a drug (on example, clinical efficacy of montelukast in an anti-asthmatic therapy in pediatric patients). Materials and methods: The data on prescribed regimens was retrospectively extracted from the inpatient records of 608 BA patients admitted to hospital in 2014-2015. Mathematical evaluation was based on the risk factor concept. Results and discussion: The absolute efficacies (AEs) was estimated to be 91.85% (95% CI 90.15-93.55%) in the exposed group; the attributable efficacy (AtE) was found to be 17.00% (95% CI 10.91-23.09%); the relative efficacy (RE) was found to be 1.23 (95% CI 0.21-2.24); and the population attributable efficacy (PAtE) was found to be 7.55% (95% CI 2.49-12.61%). Conclusions: The AtE, RE, and PAtE were statistically significant. The RE was found to be 1.23. However, the lower limit of its 95% CI (0.21-2.24) was less than 1, indicating that the increase in clinical efficacy was not found to be statistically significant. In the studied sample positive outcome rates were 91.85% (95% CI 90.15-93.55%) in the exposed group and 74.85% (95% CI 72.49-77.21%) in the comparator group. He presented methodology for determining the correlation of the clinical efficacy of the pharmacotherapy regimen with the addition of a drug can be successfully applied in the future.